Computer simulation of the spatial structure of MUC 1 peptides capable of inhibiting apoptosis - N. V. Ivanisenko; I. N. Lavrik; V. A. Ivanisenko (Вавиловский журнал генетики и селекции)
Identification of new effective inhibitors of apoptosis is an important task for drug development for treatment of a number diseases including neurogenerative diseases. Initiation of apoptosis occurs via the formationof macromolecular protein complexes. In these complexes, activation of key enzymes in apoptosis, caspases, takes place. One of those macromolecular complexes is DISC (death- inducing signaling complex) playing a central role in the induction of the extrinsic apoptosis pathway. The adaptor protein FA DD has a major role in the formation of the DISC. Therefore, inhibitors of FA DD, preventing its function in the DISC, can act as potential drugs inhibiting apoptosis. Furthermore, the study of the mechanisms of action of these inhibitors is of great interest for understanding the mechanisms of the signal transduction pathways of apoptosis. It has been reported that a natural protein inhibitor of FA DD is mucin-type 1 glycoprotein (MUC1). In particular, two fragments of the primary structure of the cytoplasmic domain of MUC1 (MUC1- CD) are capable of inhibiting the binding of caspase-8 to FA DD. However, the three-dimensional structure of MUC1 has not been obtained yet. It complicates significantly the rational design of potential drugs on the basis of these peptides. In this context, the aim of the present study was in silico prediction ofthree-dimensional structures of MUC1-CD peptides corresponding to protein fragments (1-20 and 46-72), as well as analysis of their conformational properties. The main focus of the work was given to the peptide MUC1-CD (46-72), which is capable of binding to FA DD. Using the methods of molecular dynamics in the implicit water it was shown that the peptide MUC1-CD (46-72) can take conformations similar to the conformations of a number of fragments of the caspase-8 DED domain. It was found that  the structure of the peptide MUC1-CD (46-72) is similar to the spatial structure of at least four fragments of caspase-8. These results indicate that the molecular mechanism of the inhibitory activity of the peptide can be explained by competitive binding with FA DD due to the structural and conformational similarity with the fragments of the caspase-8 DED domain.